Efek Bahan Desinfektan dan Waktu Pengecoran Terhadap Stabilitas Dimensi Model Hasil Cetakan Silikon Kondensasi - Johan Drison; Rosalina Tjandrawinata; Octarina Octarina (Jurnal Material Kedokteran Gigi, 2014)
Impression stage is an important step in dentistry. The impression itself can be a media of infection transmisions due to microorganisms in the oral cavity. Therefore it is necessary to disinfect the impression before casting process. Dimensional stability is a factor that can affect accuracy of gypsum casts, meanwhile the elastomeric impression materials are not usually casted immediatelly. To determine effect of sodium hypochlorite and chlorhexidine gluconate disinfectans with various casting time, on the dimensional stability of condensation silicone gypsum casts. A total of 30 samples were made using condensation silicone impression materials. The impressions were disinfected in 5,25% sodium hypochlorite (NaOCl) or 0,2% chlorhexidine gluconate (Chx). The impression was casted in various time intervals 0, 12, 24, 36, and 48 hours with type III gypsum product. Dimensional changes were measured and the data obtained were analyzed using SPSS 17 with two-way ANOVA, post hoc LSD and unpaired t-test. Sodium hypochlorite caused greater dimensional changes (0,49%) than chlorhexidine gluconate (0,44%). Significant dimensional changes were detected after the casting was delayed for more than 24 hours (p <0.05). Sodium hypochlorite and chlorhexidine gluconate do not cause dimensional changes, assuming that condensation silicone impression is casted in maximum time of 24 hours. Disinfection of condensation silicone impression material in chlorhexidine gluconate presents better dimensional stability than sodium hypochlorite.